2002
DOI: 10.1071/as01042
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Radio Remnant of SN 1987A: 1990-2001

Abstract: The development of the radio remnant of SN 1987A has been followed using the Australia Telescope Compact Array since its first detection in 1990 August. The remnant has been observed at four frequencies, 1.4, 2.4, 4.8, and 8.6 GHz, at intervals of 4–6 weeks since the first detection. These data are combined with the 843 MHz data set of Ball et al. (2001) obtained at Molonglo Observatory to study the spectral and temporal variations of the emission. These observations show that the remnant continues to increase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
66
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 34 publications
11
66
2
Order By: Relevance
“…The addition of bilateral lobes approximates the morphology of the radio remnant (Gaensler et al 1997;Manchester et al 2002Manchester et al , 2005Ng et al 2008). The morphology of the X-ray remnant in the earliest epochs resembled that of the radio remnant with emission approximated by opposite bilateral regions of increased brightness.…”
Section: Bilateral Lobes + Torus Modelmentioning
confidence: 95%
See 1 more Smart Citation
“…The addition of bilateral lobes approximates the morphology of the radio remnant (Gaensler et al 1997;Manchester et al 2002Manchester et al , 2005Ng et al 2008). The morphology of the X-ray remnant in the earliest epochs resembled that of the radio remnant with emission approximated by opposite bilateral regions of increased brightness.…”
Section: Bilateral Lobes + Torus Modelmentioning
confidence: 95%
“…The goal for our empirical models is to characterize the Chandra X-ray images in a more realistic way and in a similar spirit as those of the radio studies (Gaensler et al 1997;Manchester et al 2002Manchester et al , 2005Ng et al 2008) in order to obtain a measurement for the radial expansion of the remnant. The inner ring is inclined by 43 • to the line of sight (Crotts & Heathcote 1991).…”
Section: Radial Expansionmentioning
confidence: 99%
“…The radio emission from SNR 1987A is non-thermal (Gaensler et al 1997;Manchester et al 2002) and is probably produced by relativistic electrons accelerated by the reverse shock (Manchester et al 2005). Park et al (2005) have noted that the hard X-ray light curve resembles the radio light curve of SNR 1987A and have suggested that the radio emission and the hard X-rays might have a common origin.…”
Section: Discussionmentioning
confidence: 99%
“…So far, this has been directly possible for two objects, SN1987A and SN1993J, although in some cases the deceleration can be estimated from model fitting to the radio light curves. Manchester, et al [29] have shown that the blastwave from the explosion of SN1987A traveled through the tenuous medium of the bubble created by the high speed wind of its BSG progenitor at an average speed of ~10% of the speed of light (~ 35,000 km s" 1 ), but has decelerated dramatically to only ~ 3,000 km s" 1 since it has reached the inner edge of the prominent optical ring.…”
Section: Deceleration Of Blastwave Expansionmentioning
confidence: 99%